Sustainability Management of the Lake Maninjau Area towards Environmental Pollution from the Jinayah Fiqh Perspective - Pramadinanti, Fitri (DELICTUM : Jurnal Hukum Pidana Islam, 2023)
AbstractThis research was motivated by environmental pollution in Lake Maninjau caused by floating net cage cultivation activities. This pollution is caused by sediment of fish food and dead fish carcasses which then accumulate at the bottom of the lake. The pollution of Lake Maninjau was also triggered by the rapid development of floating net cages. Regional Regulation No. 5 of 2014 concerning Sustainability Management of the Lake Maninjau Area was established in an effort to reduce pollution in the lake. Based on the background of the problem, the author wants to see the effectiveness of Regional Regulation No. 5 of 2014 concerning Sustainability Management of the Lake Maninjau Area from environmental pollution and its factors. The author will also explain the views of Islamic Criminal Law on legal sanctions contained in Regional Regulation No. 5 of 2014. This research uses field research, which is empirically juridical in nature. The author uses inductive and descriptive methods in analyzing data.Based on the research results in this thesis, the author found that the implementation of Regional Regulation No. 5 of 2014 concerning the Sustainability Management of Lake Maninjau has not been effective, seen from the development of the floating net cage business which exceeds the capacity and the quality of the lake's polluted water. The implementation of the sanctions contained in this Regional Regulation in the form of imprisonment for a maximum of 6 months or a fine of a maximum of 50 million has not been implemented because there are several factors that hinder the implementation of this Regional Regulation. Meanwhile, in the Jinayah Fiqh, sanctions for perpetrators of environmental pollution are given a ta'zir penalty where the punishment is carried out by a judge or authority, in this case the regional government.Keywords: Effectiveness, Environmental Pollution, Floating Net Cages, Lake Maninjau. AbstrakPenelitian ini dilatar belakangi karena adanya pencemaran lingkungan di Danau Maninjau yang diakibatkan oleh kegiatan pembudidayaan karamba jaring apung. Pencemaran ini disebabkan oleh endapan pakan ikan dan bangkai ikan yang sudah mati kemudian menumpuk didasar danau. Pencemaran danau Maninjau juga dipicu karena berkembang pesatnya Karamba jaring apung. Perda No. 5 Tahun 2014 Tentang Pengelolaan Kelestarian Kawasan Danau Maninjau ditetapkan dalam upaya mengurangi pencemaran di danau. Berdasarkan latar belakang masalah, maka penulis ingin melihat efektivitas Perda No 5 tahun 2014 Tentang Pengelolaan Kelestarian Kawasan Danau Maninjau dari pencemaran lingkungan beserta faktor-faktornya. Penulis juga akan memaparkan pandangan Hukum Pidana Islam terhadap sanksi hukum yang terdapat dalam Perda No 5 Tahun 2014. Penelitian ini menggunakan penelitian lapangan, yang sifatnya yuridis empiris. Adapun penulis menggunakan metode induktif dan deskriptif dalam menganalisis data.Berdasarkan hasil penelitian dalam skripsi ini, penulis menemukan bahwa belum efektifnya pelaksanaan Perda No 5 Tahun 2014 Tentang Pengelolaan Kelestarian Danau Maninjau, dilihat dari berkembangnya usaha karamba jaring apung yang melebihi daya tampung serta kualitas air danau yang tercemar. Penerapan sanksi yang terdapat dalam Perda ini berupa kurungan 6 bulan paling lama atau denda paling banyak 50 juta belum terlaksana hal tersebut karena ada beberapa faktor yang menghambat pelaksanaan Perda tersebut. Sedangkan dalam Fiqh Jinayah sanksi bagi pelaku pencemaran lingkungan diberi hukuman ta'zir yang penerapan hukumannya dilakukan oleh hakim atau penguasa, dalam hal ini pemerintah daerah.Kata Kunci : Efektivitas, Pencemaran lingkungan, Karamba Jaring Apung, Danau Maninjau